2023
DOI: 10.3390/nu15040860
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Water-Soluble Vitamins in a Group of Patients with CKD versus Interventions and Supplementation—A Systematic Review

Abstract: Background: Increasingly, chronic kidney disease (CKD) is becoming an inevitable consequence of obesity, metabolic syndrome, and diabetes. As the disease progresses, and through dialysis, the need for and loss of water-soluble vitamins both increase. This review article looks at the benefits and possible risks of supplementing these vitamins with the treatment of CKD. Methods: Data in the PubMed and Embase databases were analyzed. The keywords “chronic kidney disease”, in various combinations, are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…For instance, time after the dialysis or transplantation can be informative as PON1 activity was reported to decrease with an increase in dialysis vintage (time on dialysis in years) [56,79]. Third, the association of lifestyle factors (e.g., diets) [80,81] and prescribed drugs [82] with PON1 activity was not explored in the included studies. In this case, therapies using antioxidants (e.g., vitamins B, C, D, and E, coenzyme Q10, L-carnitine, a-lipoic acid, curcumin, green tea, flavonoids, polyphenols, omega-3 polyunsaturated fatty acids, trace elements, Nacetylcysteine) might also be considered as the antioxidant supplementation is being studied to ameliorate oxidative stress in patients receiving HD and PD [83].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, time after the dialysis or transplantation can be informative as PON1 activity was reported to decrease with an increase in dialysis vintage (time on dialysis in years) [56,79]. Third, the association of lifestyle factors (e.g., diets) [80,81] and prescribed drugs [82] with PON1 activity was not explored in the included studies. In this case, therapies using antioxidants (e.g., vitamins B, C, D, and E, coenzyme Q10, L-carnitine, a-lipoic acid, curcumin, green tea, flavonoids, polyphenols, omega-3 polyunsaturated fatty acids, trace elements, Nacetylcysteine) might also be considered as the antioxidant supplementation is being studied to ameliorate oxidative stress in patients receiving HD and PD [83].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinamide may be associated with side effects such as hot flashes, thrombocytopenia, hepatoxicity, gastrointestinal symptoms, and increased serum uric acid [ 61 , 63 ]. Recently, some studies have indicated that niacin supplementation with 400-1000 mg is necessary to appropriately lower phosphate levels [ 5 ]. Therefore, there is no hard evidence at this time to justify vitamin B3 supplementation.…”
Section: Effect and Supplementation Of B Vitaminsmentioning
confidence: 99%
“…This is particularly likely in patients with CKD because they may often be prescribed these medications, and they show lower vitamin B6 intake with increased demand. These data suggest that patients with stage 3 or higher CKD are at an increased risk of vitamin B6 deficiency and should therefore take the appropriate supplementation to reduce CV risk [ 5 , 38 ]. Both the European Society for Parenteral and Enteral Nutrition and Australian Care guidelines for renal failure recommend that vitamin B6 be supplemented daily at a dose of 5 mg [ 59 , 64 , 65 ].…”
Section: Effect and Supplementation Of B Vitaminsmentioning
confidence: 99%
See 2 more Smart Citations